PENGARUH ICT DAN PROMOSI ONLINE TERHADAP KEPUTUSAN PEMBELIAN (STUDI KASUS PADA MAHASISWA PRODI SISTEM INFORMASI UNIKOM PENGGUNA ONLINE SHOP) - Susilawati, Erna; Dhaniawaty, Rani Puspita (Universitas Komputer Indonesia, 2019)
The existence of online marketing (e-marketing) cannot be separated from the rapid development of information, communication and technology. Gadgets, smart phones and laptop also the support of internet connection that can open new business field and are interested by people. Because of buying something via online shop is considered more practical and does not waste a lot of time and energy. So that it effect to the consumer purchasing decisions. The aims of this research are to find the significant relation between ICT and online promotion towards purchasing decision. This research used quantitative method by using multiple linear regression, SPSS. The result of this research showed there is significant effect between ICT (X1) towards purchasing decision (Y). it can be seen from the coefficient regression value about 0,425, however the online promotion (X2) has the significant effect towards purchasing decision (Y). It can be seen by the value of regression coefficient about 0,842. Whereas both variable ICT (X1) and online promotion (X2) as the independent variable have joint effect towards purchasing decision about 86,2% while the rest about 13,8% is effected by the other variables that is not examined in this study. Key words: ICT, e-marketing, purchasing decisions